Diversity of Soil Insect in Kerandangan Ecotourism Nature Park Area West Lombok Island - Mery Rosinta; I Putu Artayasa; Mohammad Liwa Ilhamdi (Jurnal Biologi Tropis, 2021)
The role of soil insects is very important as environmental indicator organisms, balancing ecosystems, and helping the process of soil decomposition. This study aims to determine the diversity of soil insects in the Kerandangan Ecotourism Nature Park (ENP) West Lombok. The diversity of flora and fauna that it has makes ENP Kerandangan suitable as an ecotourism area that offers interesting tourist objects as well as educational facilities. Sampling was carried out using the pitfall trap method. Samples were taken at three stations. The first station is in the southern forest of Kerandangan Nature Tourism Park, the second station is in the middle and the third station is in the north forest of Kerandangan Nature Tourism Park. Data were analyzed using the Shannon-Wiener diversity index. The results showed that there were 12 types of insects belonging to 7 orders and 11 families, totaling 595 individuals. Insect species were dominated by insects from the family Carabidae, namely the genus Harpalus as many as 178 individuals. In general, the index value of soil insect species diversity in the Kerandangan TWA forest area is 1.768. The highest species diversity index value was at station 2, namely H'= 1.772. while the lowest is at station 3, namely H'=1.488. In conclusion, the diversity of soil insects in the Kerandangan Nature Tourism Park, West Lombok, varied at each station and in general the level of soil insect diversity in the Kerandangan Nature Tourism Park was categorized as moderate.